Handbook of Human Motion (Springer International Publishing, 2018)
The Handbook of Human Motion is a large cross-disciplinary reference work which covers the many interlinked facets of the science and technology of human motion and its measurement. Individual chapters cover fundamental principles and technological developments, the state-of-the-art and consider applications across four broad and interconnected fields; medicine, sport, forensics and animation. The huge strides in technological advancement made over the past century make it possible to measure motion with unprecedented precision, but also lead to new challenges. This work introduces the many different approaches and systems used in motion capture, including IR and ultrasound, mechanical systems and video, plus some emerging techniques. The large variety of techniques used for the study of motion science in medicine can make analysis a complicated process, but extremely effective for the treatment of the patient when well utilised. The handbook descri bes how motion capture techniques are applied in medicine, and shows how the resulting analysis can help in diagnosis and treatment. A closely related field, sports science involves a combination of in-depth medical knowledge and detailed understanding of performance and training techniques, and motion capture can play an extremely important role in linking these disciplines. The handbook considers which technologies are most appropriate in specific circumstances, how they are applied and how this can help prevent injury and improve sporting performance. The application of motion capture in forensic science and security is reviewed, with chapters dedicated to specific areas including employment law, injury analysis, criminal activity and motion/facial recognition. And in the final area of application, the book describes how novel motion capture techniques have been designed specifically to aid the creation of increasingly realistic animation within films and v ideo games, with Lord of the Rings and Avatar just two examples. Chapters will provide an overview of the bespoke motion capture techniques developed for animation, how these have influenced advances in film and game design, and the links to behavioural studies, both in humans and in robotics. Comprising a cross-referenced compendium of different techniques and applications across a broad field, the Handbook of Human Motion provides the reader with a detailed reference and simultaneously a source of inspiration for future work. The book will be of use to students, researchers, engineers and others working in any field relevant to human motion capture.